New and emerging therapies for Clostridium difficile infection. Issue 6 (December 2016) - Martin, Jessica; Wilcox, Mark
Abstract : Purpose of review: Clostridium difficile infection has attained high prominence given its prevalence and impacts on patients and healthcare institutions. Multiple new approaches to the prevention and treatment of C. difficile infection (CDI) are undergoing clinical trials. Recent findings: Bezlotoxumab is a monoclonal antibody against toxin B that has successfully completed phase III studies, demonstrating a significant reduction in recurrent CDI when given with standard of care antibiotics. Antibiotics under development include cadazolid and ridinilazole, whereas surotomycin has had disappointing phase III results. Multiple live biotherapeutics are being developed, including freeze thawed and encapsulated versions of faecal microbiota transplantation to improve the practicality of treating patients with recurrent CDI. Alternatives to faecal microbiota transplantation, that aim to improve safety, including a microbial suspension, RBX2660, and a complex spore formulation, SER-109, have progressed to phase II studies. A nontoxigenic C. difficile strain has also shown promise to prevent recurrent CDI. In addition, three C. difficile vaccines have progressed to phase II/III clinical trials. Summary: The diverse approaches to treating and preventing CDI offer substantial promise that new treatment options will soon emerge, particular ones that reduce the risk of recurrences.